Diseño de una máquina para producir ductería circular con grafado en espiral (spiroducto) para la empresa Aconaire S.A.S. (2019)
The present project was developed in order to offer an alternative design of a machine to manufacture ductwork with spiral graffing, taking into account all the parameters that are required for the most appropriate development in terms of calculations and sizing of the machine, also having the support of different standards such as ASHRAE and SMACNA, being the most influential within the development of the project and also the requirements offered by the company Aconaire SAS; which aims to improve the manufacturing process of the circular duct.